Strategi Pemasaran Pinang (Areca sp.) Studi Kasus Kecamatan Sibolangit, Kabupaten Deli Serdang, Propinsi Sumatera Utara - Pebriaman Kanista M; Yunus Afifuddin; Ridwanti Batubara (Peronema Forestry Science Journal, 2015)
Areca nut is one of North Sumatra’s potential export commodity which it’s management still did as partial. The purpose of this research is analyzing the income level of areca nut farmers, analyzing the commodity marketing system of areca nut, Identifying factors marketing development of areca nut in Sibolangit sub Deli Serdang regency North Sumatra Province. The election of research’s location did expressly. The decision of respondent did as purposive sampling, but processing factory and business administration which involved did as snowball sampling method with total sample of 38 (thirty eigth) respondents. Data collected through observation and analysis of the problem with interview using  questionnaires to farmers and entrepreneurs nut. Overall both primary and secondary data is tabulated next as needed. Result of this research is cultivation of areca nut did as polycultur with low technology application level will low productivity. In product marketing subsystem, trade chain is too long, that’s why product’s cost is not too efficient and than make double margin, than areca nut’s farmer price is too low, so areca marketing strategy priorities in District Sibolangit is forming farmer groups, cooperative village level, supervision of areca marketing system, human resource development and used of quality seeds. Keywords: management, marketing, areca nut and marketing strategy